Analysis of Code-Mixing by The Bali Arknights Players Community on WhatsApp - Kadek Risma Septiani; Dewa Putu Ramendra; I Wayan Swandana (Journal of Educational Study, 2026)
This study investigates the phenomenon of code-mixing within the WhatsApp interactions of the Bali Arknights Players Community. The primary objective is to identify the types of code-mixing based on Hoffmann’s (1991) classification. Employing a descriptive quantitative design, this research analyzed 168 instances of code-mixing extracted from group chat transcripts. The findings reveal three types of code-mixing: intra-sentential, intra-lexical, and involving a change of pronunciation. Intra-sentential code-mixing was the most dominant type, accounting for 74.40% of the data, followed by intra-lexical code-mixing at 21.43%, while code-mixing involving a change of pronunciation represented only 4.17%. The dominance of intra-sentential code-mixing indicates that community members more frequently insert English words or phrases into Indonesian sentence structures rather than hybridizing words or modifying phonological forms. This pattern reflects the influence of gaming terminology, which is predominantly expressed in English and widely adopted by bilingual speakers in online gaming communities. The study concludes that in specialized digital environments such as gaming communities, code-mixing functions as an effective communicative strategy to facilitate technical discussions, strengthen group identity, and maintain interactional efficiency among members.